2011
DOI: 10.4067/s0717-95022011000100028
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Pregnancy Tumor (Pyogenic Granuloma) with Extensive Alveolar Bone Loss Mimicking a Malignant Tumor: Case Report and Review of Literature

Abstract: MARTINS-FILHO SUMMARY:Oral pyogenic granuloma is a hyperplastic inflammatory lesion commonly associated to local irritation or trauma. Females are more affected than men probably due to the vascular effects of hormones that occur during puberty, pregnancy and menopause. In the pregnancy, the lesions are known as "pregnancy tumor" and tend to occur more frequently during the second and third trimester. In the oral cavity, histopathological examination is required for diagnosis, since the lesion is clinically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
2
18
0
1
Order By: Relevance
“…In a study done by Bhrugesh, Singh and Shenoy, cases of oral pyogenic granulomawith alveolar bone loss have been reported. MartinsFilho,reported a case of aggressivepyogenic granuloma with extensive alveolar bone loss that resembled a Malignant Tumor [9] . This emphasizes the need for histopathological evaluation, for any clinically or radiographically suspected lesion of pyogenic granuloma, to rule out the possibility of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Bhrugesh, Singh and Shenoy, cases of oral pyogenic granulomawith alveolar bone loss have been reported. MartinsFilho,reported a case of aggressivepyogenic granuloma with extensive alveolar bone loss that resembled a Malignant Tumor [9] . This emphasizes the need for histopathological evaluation, for any clinically or radiographically suspected lesion of pyogenic granuloma, to rule out the possibility of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Bhrugesh, 12 Singh, 13 and Shenoy, 14 reported cases of oral pyogenic granuloma with alveolar bone loss. Martins-Filho, 15 reported aggressive pyogenic granuloma with extensive alveolar bone loss mimicking a Malignant Tumour. Saravana 16 in his review of 137 cases reported four patients with extensive bone loss and mobility of teeth.…”
Section: Aggressive Invasive Oral Pyogenic Granuloma Case Report 83mentioning
confidence: 98%
“…In pregnancy tumors, the increased hormons return their normal ranges and tumor disappaers spontaneously after pregnancy. Pregnancy tumors are generally observed after first trimester 15,17,18 . Many published case studies have been reported on the observation of pregnancy tumors show that it can be seen in the third trimester likewise 2,3,19 .…”
Section: Discussionmentioning
confidence: 99%
“…For constructing therapy protocol, pregnancy should be taken into consideration. An expectant manner is followed but if the lesion causes bleeding, chewing disorders and does not recess after birth surgical treatment is indicated 15,19 . Operation during pregnancy is not a preferred therapy method since it shows recurrency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation